Effects of three different host plants on two sex life table parameters of the fall armyworm Spodoptera frugiperda - Zhao Wang; Huan Zhu; Dao-Chao Jin; Jin-Ting Hou; Xia Liu (Scientific Reports)
Abstract The fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) is a major phytophagous pest that invaded China in late 2018, posing a serious threat to local agricultural production. Therefore, we investigated the effects of maize, soybean, and sweet potato on the growth, development, and reproduction of S. frugiperda under laboratory conditions. The developmental period of the egg-larval stage was significantly longer when S. frugiperda fed on sweet potato (28.94 days) compared to maize (16.19 days) and soybean (17.82 days). Sweet potato feeding significantly prolonged the pupal period, but this effect was not observed in the adult stage. Spodoptera frugiperda larvae fed on sweet potato had the lowest pupal weight (116.18 mg) and pupation rate (68.19%). The mean fecundity of females significantly differed among the plants, with egg production being highest for insects fed on maize (996.17 eggs) and lowest for those fed on sweet potato (319.28 eggs). Spodoptera frugiperda fed on sweet potato exhibited the smallest net reproductive rate (47.892), lowest intrinsic rate of increase (0.083 day−1), lowest finite rate of increase (1.086 day−1), and longest mean generation time (46.806 days). Overall, S. frugiperda can survive and complete its entire life cycle on all three host plants.